A Reversal in Hair Cell Orientation Organizes Both the Auditory and Vestibular Organs - Tarchini, Basile (Frontiers in Neuroscience, 2021)
Sensory hair cells detect mechanical stimuli with their hair bundle, an asymmetrical brush of actin-based membrane protrusions, or stereocilia. At the single cell level, stereocilia are organized in rows of graded heights that confer the hair bundle with intrinsic directional sensitivity. At the organ level, each hair cell is precisely oriented so that its intrinsic directional sensitivity matches the direction of mechanical stimuli reaching the sensory epithelium. Coordinated orientation among neighboring hair cells usually ensures the delivery of a coherent local group response. Accordingly, hair cell orientation is locally uniform in the auditory and vestibular cristae epithelia in birds and mammals. However, an exception to this rule is found in the vestibular macular organs, and in fish lateral line neuromasts, where two hair cell populations show opposing orientations. This mirror-image hair cell organization confers bidirectional sensitivity at the organ level. Here we review our current understanding of the molecular machinery that produces mirror-image organization through a regional reversal of hair cell orientation. Interestingly, recent evidence suggests that auditory hair cells adopt their normal uniform orientation through a global reversal mechanism similar to the one at work regionally in macular and neuromast organs. Macular and auditory organs thus appear to be patterned more similarly than previously appreciated during inner ear development.